The drag effect of carbon emissions on China’s economic growth under 2030 carbon emission reduction target - Xu, Jing; Zhu, Mengxin; Che, Xiaojing (Frontiers in Environmental Science, 2025)
The 2020 Climate Ambition Summit (CAS) was a multilateral process that brought together the international community to strengthen climate action. During the summit, the Chinese government pledged to reduce the CO2 emission levels per unit GDP seen in 2005 by more than 65% by 2030. Trade-off between carbon reduction and economic growth under 2030 carbon reduction target requires careful consideration. Using this target, we constructed a drag model of emission reduction constraints on economic growth on the basis of Romer’s classical hypothesis. Partial least-squares (PLS) regression was applied to this model to eliminate multicollinearity problems. The results show that the drag effect of carbon emissions (CEs) on economic growth is 0.0378. It indicates that if China were to fulfill 2030 emission reduction target pledged at the CAS, there would be an average annual GDP reduction of more than 3.78%, influenced by existing technology and structural parameters for the production function. We also present suggestions for promoting the green technological innovation and improving production efficiency.